2017
DOI: 10.1088/2053-1583/aa86de
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional crossover of the charge density wave transition in thin exfoliated VSe 2

Abstract: The capability to isolate one to few unit-cell thin layers from the bulk matrix of layered compounds 1 opens fascinating prospects to engineer novel electronic phases. However, a comprehensive study of the thickness dependence and of potential extrinsic effects are paramount to harness the electronic properties of such atomic foils. One striking example is the charge density wave (CDW) transition temperature in layered dichalcogenides whose thickness dependence remains unclear in the ultrathin limit 2-5 .Here … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 42 publications
14
72
0
Order By: Relevance
“…3(c) in which one can recognize a two-peaked structure persisting up to T = 120 K. Since the two-peaked structure disappears above 140 K, it is inferred that the gap starts to open at around this temperature. It is remarked that the observed TCDW (140 K) of monolayer VSe2 is in agreement with the recent study on a MBE-grown monolayer film [16], but is apparently higher than those of both bulk (~ 110 K) and exfoliated multilayer thin films (< 130 K) [14,15] As shown in Fig. 3(b), the EDC of b pocket (point B) at T = 40 K exhibits a leading-edge shift similarly to the a pocket, whereas the overall spectral feature is much broader and a pseudogap-like structure with an energy scale of ~200 meV is observed as indicated by a black circle in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3(c) in which one can recognize a two-peaked structure persisting up to T = 120 K. Since the two-peaked structure disappears above 140 K, it is inferred that the gap starts to open at around this temperature. It is remarked that the observed TCDW (140 K) of monolayer VSe2 is in agreement with the recent study on a MBE-grown monolayer film [16], but is apparently higher than those of both bulk (~ 110 K) and exfoliated multilayer thin films (< 130 K) [14,15] As shown in Fig. 3(b), the EDC of b pocket (point B) at T = 40 K exhibits a leading-edge shift similarly to the a pocket, whereas the overall spectral feature is much broader and a pseudogap-like structure with an energy scale of ~200 meV is observed as indicated by a black circle in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Recently it was reported that exfoliation of bulk crystal leads to an intriguing change in TCDW; i.e. TCDW gradually decreases with reducing the number of layers [14], but suddenly exhibits a characteristic upturn at around the film thickness of 10 nm, reaching ~130 K much higher than bulk TCDW (110 K) [15]. Further, very recently, monolayer VSe2 was fabricated and the low energy electron diffraction (LEED), angle-resolved photoemission spectroscopy (ARPES) and scanning tunneling microscopy (STM) have revealed that the TCDW is enhanced in monolayer (~140 K) compared to bulk [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to a wave vector of Q 1 = (1/4, 0, 2/3) (in units of reciprocal lattice vectors). This wave vector and the equivalent ones, related by symmetry, suggest a CDW periodicity of 4 a × 1 a × 3 c , 1 a × 4 a × 3 c , or 4 a × 4 a × 3 c , in agreement with reports for bulk VSe 2 [83,84], and unstrained thin layered samples [51]. We have checked the phonon frequencies at the Γ point for these phases and find that they are non-imaginary.…”
Section: Theory and Energetics Of Cdw States In Vse2supporting
confidence: 90%
“…First-principles calculations identify this additional CDW state to be consistent with soft modes in the normal-state phonon dispersion and as a competing low energy state to the conventional 4 a ×4 a CDW. We note that a conventional 4 a ×4 a CDW was observed in thin (10 nm) exfoliated VSe 2 layered samples [51]. This indicates the strain in our epitaxial film plays an important role in the rise of the unconventional 4 a ×√3 a CDW.…”
Section: Introductionmentioning
confidence: 78%
“…In some cases, the monolayer of these materials may exhibit new properties compared to their bulk counterpart, for example, ferromagnetic ordering has been observed in monolayer VSe 2 while the bulk is paramagnetic to low temperatures . Moreover the CDW order temperature may be different for mono‐ and few‐layer samples compared to that of the bulk …”
Section: Introductionmentioning
confidence: 99%